Commercialising subsistence farmers: a benefit or detriment to the poor? - Taruvinga, Maita (My University, 2011)
The commercialisation of subsistence farmers: a benefit or detriment to the poor? The aim of this study is to understand if rural households in Swaziland are benefiting from engaging in commercial outgrower schemes. The process of commercialising subsistence farmers has been one of the government of Swaziland’s strategic attempts to lift rural households out of poverty by raising their income levels. I explore some of the socioeconomic factors that are imposed on rural households, bringing into question whether or not this strategy is a viable poverty alleviation policy. In Sub-Saharan Africa, agriculture has been central to economic development through the promotion of the export of crops and raw material. Its profitable potential provides a vehicle for using land in rural areas for poverty alleviation and rural development strategies. Commercialising subsistence farmers has the potential to offer the prospect of raising incomes, improving welfare, food security and nutritional status that could otherwise have been worse. However, this transition (from subsistence to commercial) in agricultural activities in rural communities can also have detrimental consequences such as reduce income and threaten household food security. I therefore ask the question: How have rural households benefited from engaging in commercial agriculture? In this study I explore the process of commercialising subsistence farmers as a form of rural development. To achieve this, I have carried out a case study analysis of a rural community in Swaziland called Mafucula, which has currently been involved in the commercial agriculture of sugarcane for the last six years. Empirical data was obtained through semi-structured interviews with 30 households in this community. My findings demonstrate that with six years into commercial agriculture, this community has not benefited from this venture and continues to face the ongoing struggle of poverty.